Impact of Artificial Intelligence on the Single Market for Digital Content - Renáta Bačárová (Acta Universitatis Carolinae. Iuridica)
The paper deals with the provision of digital content in the Digital Single Market with particular attention to the protection of creators’ rights. The issue is examined in the context of the new phenomenon of artificial intelligence. The research focuses on the legal assessment of the input used to train an AI system and the output obtained from it with regard to the legality of the source and copyright protection. The use of exceptions and limitations, especially text and data mining, appears to be essential. It is also important to assess the legal nature of AI-generated output from a copyright perspective. Innovative solutions to protect authors’ rights against unauthorized use of AI training works and to exclude them from the training data (e.g. “Have I Been Trained” website, DRM, data poisoning) are discussed. The paper polemics over the introduction of sui generis protection for AI creations.